Cross-flow non-equilibrium model of air sparging: numerical and analytical solutions - Al-Gahtani, Osama S., author (Colorado State University. Libraries, 2006)
According to the Environmental Protection Agency (EPA), air sparging is the most developed innovative in-situ technology for remediation of sites which have groundwater contaminated by volatile organics. Air sparging systems are easy to implement, and relatively simple to operate. In addition, it is a relatively low cost remediation technology that can be applied in conjunction with other remediation technologies. For these reasons, air sparging has become widely used. However, air sparging is still considered as an unproven technology by the EPA. The objective of this study is to investigate various "rule of thumb" design protocols for air sparging using a cross-flow two-compartment numerical model to improve the efficiency of air sparging. For example, one of the major design elements of an air sparging system is the air-to-water ratio. Too high an air flow rate results in the development of air tubes, which decreases the area of contact between the air and the water. In other cases, it causes desaturation of porous material, which potentially results in the contaminated groundwater flowing around rather than through the active zone of remediation. In this study, the effective air-to-water ratio in an air sparging application was evaluated. A numerical model developed as a part of this study was concurrently used with the multiphase flow software Subsurface Transport Over Multiple Phase (STOMP), developed by Pacific Northwest National Laboratory. STOMP was used to calculate the reduction in the hydraulic conductivity of the water phase due to the presence of air and this output was used in the developed model. The developed model for air sparging considers the contaminant concentrations in the two compartments: gas and dissolved phases based on two-film resistance theorem. Mass balance has been applied for deriving a pair of linked partial differential equations in the gas and liquid phases. A numerical technique solution using the finite difference method has been used simultaneously in solving the two differential equations for the contaminant concentration in both gas and liquid phases. Finally, an analytical solution has been derived and verified with the numerical solution.
Keywords: civil engineering; hydrology; environmental engineering; hydrologic sciences